A new service life prediction of reinforced concrete structures due to chloride-induced cover cracking with the confinement effect - Sabtu @ Othman, Hilyati (2021)
Corrosion in reinforcing steel is an important mechanism that reduces the service life of reinforced concrete (RC) structures exposed to the marine environment. It is essential to produce an advanced method that assists in making reliable predictions for the service life of RC structures to assist cost-effectiveness in life span of asset management. This thesis aims to develop a probabilistic-based model to predict the probability of damage in RC structures due to chloride-induced concrete cover cracking. The probabilistic model developed in this thesis considers modifying the existing crack propagation model previously developed by Mullard and Stewart (2011). This research improved the existing crack propagation model by conducting two series of accelerated corrosion tests based on bidirectional (two-way) RC slab specimens. The modified crack propagation model is proposed by considering the effects of reinforcement confinement and spacing of reinforcing bars. The key variables in the crack propagation model are spatial random variables. Partly due to the variability in the quality of workmanship, environmental and material. One of the required statistical parameter for spatial variables include the scale of fluctuation. Since the data for the scale of fluctuation is scarce, the second major finding from this study is to propose a new value of the scale of fluctuation for concrete compressive strength using the Curve fitting method and the Kriging method. Finally, the modified crack propagation model for predicting the crack propagation time was then developed, then the most reliable value for the scale of fluctuation of concrete compressive strength was determined. The modified crack propagation model and the new scale of fluctuation of concrete compressive strength are used to predict the service life of RC structures due to chloride-induced cracking. By modelling spatial variability and incorporation with the Monte Carlo simulation method, the probability of corrosion damage can be measured at any time during the service life of RC structures.